Stress of emergency physicians during helicopter operations: impact of patients’ diagnoses, severity of diagnoses, and physicians’ work experience - Katja Petrowski; Camila Paola Malkewitz; Christian Schöniger; Mark Frank; Lorenz Theiler (BMC Emergency Medicine, 2023)
Abstract Purpose Emergency physicians are in danger of developing illnesses due to stress in their demanding work environment. Until today, scholars have not identified stressors or resilience factors that qualify to promote the preservation of emergency physicians’ well-being. Therefore, potential influencing variables such as patients’ diagnoses, the severity of diagnoses, as well as physicians’ work experience have to be considered. The present study aims at investigating emergency physicians in the Helicopter Emergency Medical Service (HEMS)’ autonomic nervous system activity during emergency operations in one shift with respect to patients’ diagnoses, severity of diagnoses, and physicians’ work experience. Methods Measurement of HRV (employing the parameters RMSSD and LF/HF) for 59 EPs (age: M = 39.69, SD = 6.19) was performed during two complete air-rescue-days, the alarm and landing phase being investigated in particular. Besides patients’ diagnoses, the National Advisory Committee for Aeronautics Score (NACA) was included as an indicator for severity. Diagnoses’ and NACA’s effect on HRV were examined using a linear mixed model. Results Both HRV parameters indicate a significant decrease of the parasympathetic nervous system as a function of the diagnoses. Furthermore, high NACA scores (≥ V) predicted a significantly lower HRV. In addition, a lower HRV/RMSSD with increasing work experience was observed as well as a positive association between physicians’ work experience and sympathetic activation (LF/HF). Conclusion The present study showed that pediatric diagnoses as well as time-critical diagnoses are most stressful and have the highest impact on the physicians’ ANS. This knowledge allows the development of specific training to reduce stress.